Pengaturan Terkait Kegiatan Membuka Lahan Melalui Pembakaran - Sari, Ni Luh Purnama; Sudharma, Kadek Januarsa Adi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Abstract : This research aims to analyze regulations regarding land clearing activities through burning. The method used is normative research. Regulations related to land burning are outlined in Law Number 32 of 2009 on Environmental Protection and Management, particularly Article 69, paragraph (1), letter h. However, exceptions are specified in Article 69, paragraph (2), which contradicts Article 56, paragraph (1) of the Plantation Law, prohibiting plantation operators from clearing or cultivating land by burning. This indicates that the Plantation Law does not allow for land clearing through burning, conflicting with the concept in Environmental Law. The norm conflict between Article 69 of Environmental Law and Article 56 of Plantation Law can be resolved using the principle of lex posteriori derogate legi priori, prioritizing the provisions of the Plantation Law. Therefore, in Indonesia, a rule exists that prohibits land clearing by burning without exceptions. Criminal penalties for land burning are governed by several laws, including the Criminal Code, Forestry Law, Plantation Law, and Environmental Law. The subjects of this crime include individuals and legal entities, meaning both individuals and corporations can be held accountable for environmental crimes. Under the Plantation Law, land clearing through burning can lead to a maximum prison sentence of 10 years and fines up to IDR 10,000,000,000 (ten billion rupiah).   Abstrak :  Penelitian ini bertujuan untuk menganalisis pengaturan terkait pembukaan lahan melalui pembakaran dengan menggunakan metode penelitian normatif. Regulasi tentang kegiatan ini diatur dalam Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup, khususnya Pasal 69 ayat (1) huruf h, yang juga memiliki pengecualian dalam Pasal 69 ayat (2). Namun, ketentuan ini bertentangan dengan Pasal 56 ayat (1) UU Perkebunan, yang melarang pelaku usaha perkebunan untuk membuka lahan dengan cara membakar. Ini menunjukkan bahwa UU Perkebunan tidak memberikan ruang untuk pembukaan lahan dengan cara pembakaran, bertentangan dengan konsep UU Lingkungan Hidup. Konflik antara Pasal 69 UU Lingkungan Hidup dan Pasal 56 UU Perkebunan dapat diselesaikan dengan asas lex posteriori derogate legi priori, yang mengedepankan ketentuan UU Perkebunan. Dengan demikian, di Indonesia berlaku larangan pembakaran lahan tanpa pengecualian. Hukuman pidana bagi pelanggar diatur dalam beberapa undang-undang, termasuk KUHP, UU Kehutanan, UU Perkebunan, dan UU Lingkungan Hidup. Pelaku tindak pidana ini meliputi individu dan badan hukum, sehingga terdapat tanggung jawab perorangan dan korporasi. Pelanggaran di bawah UU Perkebunan dapat dikenakan hukuman penjara maksimal 10 tahun dan denda hingga Rp 10.000.000.000 (sepuluh miliar rupiah). Penelitian ini menekankan pentingnya kepatuhan terhadap regulasi lingkungan dan konsekuensi hukum bagi pelanggar.